A cross-cultural study of staying reasons of American brands: Analysis of millennial Muslim consumers. Issue 1 (4th March 2019) - Saeed, Munazza; Azmi, Ilhaamie Abdul Ghani
Abstract : Purpose: Although researchers have investigated thoroughly the consumer's brand switching behaviour, the probability of confusion regarding "brand switching" is a less travelled road so far. Therefore, the purpose of current study is to investigate and highlight the underlying convincing parameters in relation to not switching from American brands within the context of millennial Muslim consumers in Pakistan and Malaysia. Design/methodology/approach: Data were collected from 704 consumers living in two divergent cultures, who were asked about American brands. Two categories of "reasons to stay" were examined: switching barriers and affirmatory factors. Findings: The main discovery was that staying reasons for specific brands could be different in two different cultures, but they influence the ultimate brand switching behaviour. Practical implications: This study is important for those firms who have many prospective switchers because it is important to understand why these customers stay and discover to what extent such firms can discourage such consumers from leaving, in both positive and negative ways. Originality/value: This is the first paper of its kind that examines the brand switching behaviour of millennial Muslim consumers.